Characterization of Cardiovascular Alterations Induced by Different Chronic Cisplatin Treatments - Herradón, Esperanza; González, Cristina; Uranga, José A.; Abalo, Raquel; Martín, Ma I.; López-Miranda, Visitacion (Frontiers in Pharmacology, 2017)
In the last years, many clinical studies have revealed that some cisplatin-treated cancer survivors have a significantly increased risk of cardiovascular events, being cisplatin-induced cardiovascular toxicity an increasing concern. The aim of the present work was to evaluate the cardiovascular alterations induced by different chronic cisplatin treatments, and to identify some of the mechanisms involved. Direct blood pressure, basal cardiac (left ventricle and coronary arteries) and vascular (aortic and mesenteric) functions were evaluated in chronic (5 weeks) saline- or cisplatin-treated male Wistar rats. Three different doses of cisplatin were tested (1, 2 and 3 mg/kg/week). Alterations in cardiac and vascular tissues were also investigated by immunohistochemistry, Western Blot and or quantitative RT-PCR analysis. Cisplatin treatment provoked a significant modification of arterial blood pressure, heart rate and basal cardiac function at the maximum dose tested. However, vascular endothelial dysfunction occurred at lower doses. The expression of collagen fibers and conexin-43 were increased in cardiac tissue in cisplatin-treated rats with doses of 2 and 3 mg/kg/week. The expression of endothelial nitric oxide synthase was also modified in cardiac and vascular tissues after cisplatin treatment. In conclusion, chronic cisplatin treatment provokes cardiac and vascular toxicity in a dose-dependent manner. Besides, vascular endothelial dysfunction occurs at lower doses than cardiac and systemic cardiovascular toxicity. Moreover, some structural changes in cardiac and vascular tissues are also patent even before any systemic cardiovascular alterations.